Evaluation of the MicroRNA184 Levels in Women with Miscarriage Association with Toxoplasmosis, Rubella, and CMV Infections - Sarah A. Mahmood; Salwa S. Muhsin; Rawah A. Faraj (Bogor Agricultural University, Indonesia, 2026)
MiR-184 plays a significant regulatory role in immunity during pregnancy. Its dysregulation in toxoplasmosis and rubella infection is strongly associated with increased risk of abortion . Further clinical studies are needed to validate miR-184 as a diagnostic marker and therapeutic target in pregnancy complications. One hundred specimens of blood were taken from the miscarriage ladies, with age ranges between 15 and 50 years, who were complaining of TORCH infections. The findings showed that the age range group (<20-29 years) was the highest at (59.0%), followed by (30-39 years) at (36.0%), and then (40-46 years) 5 (5.0%). Distribution of infections according to residency showed the patients that living in rural areas were higher 59 (59.0%) than those who lived in urban areas (41.0%), while the number and percentage of acute infections with rubella were higher 29 (29%) than toxoplasmosis (4.0%) in aborted women with TORCH infections. However, 4 (4.0%) of Toxoplasmosis was recorded compared to 0 (0.0%) CMV infection. The evaluation of IgM antibodies showed that Rubella IgM levels were higher at 29 (29.0%) in comparison to CMV IgM levels of 0 (0.0%). The number and percentage of rubella IgM levels among the age group (<20-29) were higher (18.0%) than in other age groups, while it was (9.0%) among the age group (30-39) years and 4 (4.0%) among Toxoplasmosis. Out of 100 patients, gene expression of MicroRNA-184 was done on 33 patients, and the results revealed that 10 (27.2%) of the aborted women were carriers of Toxoplasmosis, CMV, and Rubella IgM, and they had positive MicroRNA-184.